An Enriched -μ Model as Fading Candidate - Ferreira, Johannes Theodorus (2020)
National Research Foundation, South Africa (SRUG190308422768 nr. 120839), the South African NRF SARChI Research Chair in Computational and Methodological Statistics (UID: 71199), the South African DST-NRF-MRC SARChI Research Chair in Biostatistics (Grant no. 114613), the Research Development Programme at UP 296/2019, and the project UIDB/00297/2020 at UNL.